Experience of pond cultivation for red-clawed crayfish in the Astrakhan Region - O. V. Pyatikopova; I. N. Bedritskaya; D. A. Popov; R. R. Tangatarova (Известия ТИНРО)
Results of red-clawed crayfish cultivation in pond aquaculture in the Astrakhan Region are presented. Growing of Australian red-claw crayfish Cherax quadricarinatus juveniles in ponds with different distribution density and periods of cultivation within the summer-autumn seasons are analyzed and basic requirements for the pond cultivation of this species are determined. The optimal dimensions of pond are the following: area 0.1–0.5 hectares, depth 1.5–2.0 m, V-shaped bottom. Ponds with natural fodder base should be prepared in 20–30 days before placing the crayfish. Artificial fertilization is available for ponds with depleted soil by 3–5 t/ha of manure applied locally in the area of the pond water supply in 20–30 days before the placing. Zooplankton abundance can be increased with input of Cladocera culture, as Daphnia magna (Straus 1820), in amount of 100–500 g/ha. Coastal aquatic vegetation should not occupy more than 5 % of the pond area at the beginning of cultivation and 15 % by its end. Duration of juvenile crayfish growing in ponds of the Astrakhan Region is limited by temperature conditions (water temperature > 20 ºC is favorable for the growth) and does not exceed 115–125 days depending on the water heating. At least 100 days of growing are necessary for successful harvest. The optimal mean daily temperature of water in ponds for growing and harvesting crayfish is 23–24 ºC. Certain conditions and dates of rearing can be chosen to get certain body size of production. Small-sized juveniles with weight below 0.1 g are used for growing to the weight of 40 g in 80–100 days for the purposes of both further cultivation, replenishment of the broodstock, or sale. For producing crayfish with the weight > 40 g, juveniles with larger initial size (2–5 g) should be grown in 90–100 days. The individuals with the weight > 5 g are used as producers of planting material; at least 100 days are necessary for growth to this size. Rearing such individuals in controlled conditions (e.g. in closed water supply installations) allows to obtain the progeny in the fall of current year.